Thermo-Oxidative Stabilities of Biolubricant Blends Derived from Butter, Palm Oil, Shea Butter, and Tallow as Potential Alternatives to Fossil Oils - Lenfa, Nuhu Buhari; Anterinwa, A.; Aliyu, B. A.; Yakubu, A. (Darul Yasin Al Sys, 2025)
The growing interest in biobased lubricants presents a sustainable alternative to petroleum-derived base oils, with significant potential to reduce environmental pollution. Vegetable oils, known for their rapid biodegradability, offer promising prospects as base fluids in the formulation of environmentally friendly lubricants. However, their practical application is often hindered by inherent limitations such as poor oxidative and low-temperature stability. This study evaluates the thermo-oxidative performance of six biolubricant blends derived from Shea butter, palm oil, butter, and tallow oils. Using thermogravimetric analysis (TGA), the thermal and oxidative stability of each blend was assessed. Among the tested samples, the Shea butter–butter oil blend (SBBOL) exhibited the highest thermal and oxidative stability, with decomposition temperatures of approximately 560 °C and 450 °C at 90% weight loss, respectively. The tallow–Shea butter blend (TSBOL) demonstrated a thermal stability of 520 °C, while the butter–tallow blend showed enhanced oxidative resistance at 410 °C. Other blends, including palm oil–tallow (POTOL) and butter–tallow (BTOL), exhibited thermal stability values of 510 °C and 410 °C, respectively, with corresponding oxidative stabilities of 367 °C and 410 °C. The findings confirm that physical blending of biolubricants enhances their thermo-oxidative properties. The role of oxygen in accelerating degradation at elevated temperatures further underscores the need for optimized formulations to extend lubricant life and performance. This study contributes to the advancement of eco-friendly lubrication technologies through improved biolubricant formulation strategies.